Estimation of the reactivity of aluminum superfine powders for energetic applications; Combustion Science and Technology; Vol. 176, № 2 - Kwon Y. S.; Moon J. S.; Ilyin A. P. Aleksandr Petrovich; Gromov A. A. Aleksandr Aleksandrovich; Popenko E. M. (2004, 2004)
Title screen